15th International Conference on Concentrator Photovoltaic Systems (CPV-15) 2019
DOI: 10.1063/1.5124178
|View full text |Cite
|
Sign up to set email alerts
|

Optimum design of V-trough solar concentrator for photovoltaic applications

Abstract: This paper presents a novel design of V-trough Solar Concentrator (VSC) for low concentrator photovoltaic (CPV) applications. The conventional VSC design comprises of two flat reflectors slanted by an angle and attached to a PV module. The maximum reported concentration ratio (CR) and optical efficiency (OE) of this concentrator are 2x and 89.91%, respectively. This paper demonstrates the process of improving the VSC. The geometrical and optical performance of the conventional VSC were optimized by the theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…1 shows schematic diagram of the novel hybrid PV-TE system. The structure of the concentrator is the same as the OVSC described in [53], except that the aluminium (AL) mirrors are replaced with dichroic mirrors (DM), which enables light splitting. By using such a DM concentrator, the sunlight in the visible spectrum will be directed to a PV cell by reflection and the infrared spectrum will pass through and fall on a thermal absorber that converts light into heat for a TE module, enabling efficient utilization of solar energy over its full spectrum.…”
Section: System Description and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…1 shows schematic diagram of the novel hybrid PV-TE system. The structure of the concentrator is the same as the OVSC described in [53], except that the aluminium (AL) mirrors are replaced with dichroic mirrors (DM), which enables light splitting. By using such a DM concentrator, the sunlight in the visible spectrum will be directed to a PV cell by reflection and the infrared spectrum will pass through and fall on a thermal absorber that converts light into heat for a TE module, enabling efficient utilization of solar energy over its full spectrum.…”
Section: System Description and Experimental Setupmentioning
confidence: 99%
“…In addition, the use of commercial flat mirrors makes it impossible for direct adoption of the configuration of crossed compound parabolic concentrators (CCPC) [31,51,52]. Consequently, the structure of a modified V-trough solar concentrator (VSC) is employed, which is referred to as the "Onagraceae VSC" (OVSC) because its double-trough configuration looks like Onagraceae flowers [53]. In this work, we report a novel PV-TE hybrid system based on dichroic-mirror OVSC to concentrate the visible light to a PV cell and infrared radiation to a TE generator.…”
Section: Introductionmentioning
confidence: 99%
“…The light uniformity, U, of a concentrator is a measure of uniform light distribution in terms of the intensity over the absorber area. It can be evaluated using [52][53][54],…”
Section: Oe =mentioning
confidence: 99%
“…The theory described in section 2 was employed to determine the geometrical concentration ratio, CR geo and the aspect ratio (L/W ab ) of concentrators for a given φ. To simplify the design procedure, this study focuses on the cases of operating under normal irradiance of light (i.e., α = 0 • ) [52]. Since the PV cell to be used in this study has a dimension of 10 mm × 10 mm, the width of the absorber of the VSCs was fixed to 10 mm (i.e., W ab = 10 mm).…”
Section: Concentrator Designmentioning
confidence: 99%
“…Al-Najideen et al tested a novel double V-trough solar concentrator (DVSC) with CR greater than three suns. It is found that the PV power increased five folds at a reflector tilt angle of 71° (Al-Najideen et al 2019). Another experimental investigation was recently carried out in India on a mirror integrated PV system (MIPVS).…”
Section: Concentrating Photovoltaic Thermal Cpv/t Systemsmentioning
confidence: 99%